Recent advances in the construction of cyclic grafted polymers and their potential applications. Issue 6 (16th January 2018) - Zhang, Shuangshuang; Tezuka, Yasuyuki; Zhang, Zhengbiao; Li, Na; Zhang, Wei; Zhu, Xiulin
Abstract : Three main strategies used for the construction of cyclic grafted polymers, "grafting through", "grafting onto", and "grafting from", are summarized. Abstract : A cyclic grafted polymer, as a novel and unique kind of polymer, possesses a cyclic backbone and linear grafted side chains. Their physical properties and conformations are controlled by steric hindrance from the grafted side chains. As a cyclic derivative, cyclic grafted polymers have been successfully prepared and characterized within the past decade. To the best of our knowledge, cyclic grafted polymers have not been systematically generalized and summarized. In this review, we illustrate the considerable advances in the architectural construction of cyclic grafted polymers with three different approaches, including "grafting through", "grafting onto" and "grafting from". Additionally, their potential applications are also briefly discussed.